Psychological distress in Ghana: Are unemployed people more afflicted? - Sulemana, I.; Doabil, L.; Anarfo, E.B. (Journal of Health Psychology, 2021)
The detrimental consequences of unemployment to the psychological well-being of people have been well documented. However, much of this research has been conducted for developed countries. This study contributes to the literature by providing empirical evidence on this topic from a Ghanaian perspective. Our results revealed no significant association between unemployment and psychological distress. Rather, we found that part-time and full-time employees who were looking for a job were significantly more likely to suffer psychological distress. When we analysed the association between unemployment and psychological distress for males and females separately, we did not find a statistically significant relationship for either gender group.
Research Article
Keywords: Gender differences; Ghana; Psychological distress; psychological well-being; Unemployment